Proximal femur replacement in oncologic lesion: hemiarthroplasty vs total hip arthroplasty—a multicentric retrospective study - Matteo Salvini; Giuseppe Malerba; Cesare Meschini; Alessandro El Motassime; Edoardo Venturini; Domenico Andrea Campanacci; Francesco Muratori; Simone Checcucci; Roberto Scanferla; Raffaele Vitiello; Giulio Maccauro (Journal of Orthopaedic Surgery and Research)
Abstract Introduction This study aimed to evaluate the outcomes and complications associated with proximal femur replacement (PFR) in patients undergoing treatment for primary bone tumors or metastatic lesions. This research specifically compared modular hemiarthroplasty (HA) and total hip arthroplasty (THA) to ascertain the optimal approach regarding functionality and postoperative complications. Materials and methods A retrospective multicenter review was conducted involving 85 patients who underwent prosthetic femoral reconstruction (PFR) between the years 2015 and 2022 at two specialized medical centers. The patients were classified into two groups: 69 individuals received HA (Group A), while 16 individuals underwent THA (Group B). Outcomes were appraised utilizing the Harris Hip Score (HHS) and the Musculoskeletal Tumor Society (MSTS) score at three months post-surgery. Furthermore, the study assessed the rates of complications. Results The overall complication rate was significantly lower in HA, at 24.6%), compared to THA, at 56.3% (p = 0.03). Infection rates were substantially higher in THA, reaching 37%, as opposed to HA, which recorded a rate of 6% (p = 0.002). Although dislocation rates were elevated in THA at 25%, compared to HA at 13%, this difference did not attain statistical significance (p = 0.2). Functional outcomes revealed no significant discrepancies, with HHS and MSTS scores being comparable across both groups (HHS: HA 62 ± 25 versus THA 61 ± 16, p = 0.9; MSTS: HA 17 ± 9 versus THA 14 ± 6, p = 0.5). Logistic regression analysis identified THA as a significant risk factor for infection (odds ratio [OR] = 45.3, p = 0.008) and dislocation (OR = 6.4, p = 0.05). Conclusions Proximal femur replacement with modular hemiarthroplasty appears to provide a safer alternative to total hip arthroplasty, characterized by a lower incidence of complications and comparable functional outcomes.